Dose-escalating ruxolitinib for refractory hemophagocytic lymphohistiocytosis - Song, Yue; Li, Xiaoli; He, Xuefeng; Zhou, Fei; Du, Feng; Wang, Ziyan; Chen, Suning; Wu, Depei (Frontiers in Immunology, 2023)
Background Hemophagocytic lymphohistiocytosis (HLH) is a severe disorder characterized by excessive secretion of cytokines. Even with the recommended HLH-94/2004 regimen, over 30% of patients remain refractory to frontline therapy or relapse after an initial response, leading to poor clinical outcomes. Ruxolitinib, a JAK1/2 inhibitor targets key cytokines in HLH, has shown promising therapeutic effects. However, there has been little attention given to patients who do not respond to ruxolitinib and whether an escalating dose can provide a resolution. Methods This study analyzed eight HLH patients who received dose-escalating ruxolitinib who had previously failed to respond to the general dose. The efficacy and safety were mainly analyzed. Results Overall, four out of eight (50%) patients achieved better remission after dose escalation. Two patients who only showed improvement with the general dose achieved complete remission (CR) after dose escalation, and the other two patients also achieved CR after dose escalation when they did not respond to the general dose. The median time to achieve the best overall response was 18.5 days (IQR 13.25–23.75 days). There was no correlation of treatment outcome with blood count, liver function, LDH, cytokines, ferritin levels, NK cell activity, or the time to initiation of ruxolitinib and maximum dosage. The etiology of HLH (p=0.029) and level of sCD25 (p=0.021) correlated with treatment response to dose-escalating ruxolitinib. The area of sCD25 under the ROC curve was 0.8125 (95% CI 0.5921 to 1.033, p=0.035) when using 10,000 pg/ml as the cut-off value for predicting therapeutic effects. After a median follow-up of 159 days, two patients died, and the estimated 2-month overall survival rate was 75%. Adverse effects possibly related to the dose-escalating of ruxolitinib included two cases of extremity pain and one of aminotransferase increased. No grade 3 or higher adverse events were reported. Conclusion This is the first comprehensive study on the use of dose-escalating ruxolitinib in HLH. Ruxolitinib at an escalated dose represent a viable and relatively safe solution for managing refractory HLH. The levels of sCD25 (with a cut-off of 10000pg/ml) can serve as an indicator for early consideration of chemotherapy during treatment.